2021
DOI: 10.1002/gps.5487
|View full text |Cite
|
Sign up to set email alerts
|

The Italian national survey on Coronavirus disease 2019 epidemic spread in nursing homes

Abstract: Introduction Residents in facilities such as nursing homes (NHs) are particularly vulnerable to Coronavirus disease 2019 (COVID‐19). A national survey was carried out to collect information on the spreading and impact of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in nursing homes, and on how suspected and/or confirmed cases were managed. We carried out a survey between 25 March 2020 and 5 May 2020. Materials and Methods All Italian nursing homes either public or providing services b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…However, the nursing homes characteristics of the respondents were similar to those reported for the French Alps. Also, hospitalizations and mortality rates were comparable to other studies conducted in nursing homes and to national data [ 21 , 23 ]. Second, the ban of visits occurred 7 days before the studied period, and we cannot rule out the possibility that visitors introduced the virus prior to the ban.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…However, the nursing homes characteristics of the respondents were similar to those reported for the French Alps. Also, hospitalizations and mortality rates were comparable to other studies conducted in nursing homes and to national data [ 21 , 23 ]. Second, the ban of visits occurred 7 days before the studied period, and we cannot rule out the possibility that visitors introduced the virus prior to the ban.…”
Section: Discussionsupporting
confidence: 83%
“…This higher incidence is likely to be driven by the frailty and underlying conditions of nursing home residents, and the close living environment which may favor viral spread [ 4 , 20 ]. We observed that, as in Italy, ~30% of nursing homes faced an outbreak [ 21 ]. The hospitalization rate among residents (10% overall and 19% in facilities with outbreak) was lower than among the elderly population living in household (up to 38%) but similar to Italian reports for nursing homes [ 2 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Italian nursing homes during the "first wave" of the pandemic had to cope with multiple operational hurdles and management difficulties (i.e., a lack of personal protective equipment, an inability to have swabs tested, a lack of healthcare staff, difficulties in isolating COVID-19-infected residents, etc. ), limiting the effective and timely application of measures that may have helped in containing the spread of the virus in these settings [18,59].…”
Section: Discussionmentioning
confidence: 99%